PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH: Analisis Deskriptif di Madrasah Tsanawiyah Negeri Pasir Lawas Kabupaten Tanah Datar - Liza Martini (IAIN Batusangkar, 2016)
Implementation School-Based Management: Descriptive Analysis In Madrasah Tsanawiyah Negeri Pasir Lawas Kabupaten Tanah Datar. This research is aimed to describe the implementation of School Based Management (SBM) in which this research uses qualitative research. The background of this research is quality of education in MTsN Pasir Lawas is still low because learning and teaching process is still conducted in conventional method, learning and teaching processes still focus in teachers’ center. Meanwhile, in applying School Based Management (SBM) attains learning process based on students’ center.This study uses qualitative research methods by applying descriptive analysis to describe how the teaching and learning process in the implementation of the School-Based Management.Kata Kunci: Manajemen berbasis sekolah, proses belajar mengajar